UU-ESA science of scaling research agenda: Preliminary results from a literature review and UU-ESA survey - Schut, Marc; Mugambi, Samuel (CGIAR System Organization, 2022)
Advancing the scaling of innovation is an important driver of a successful Regional Integrated Initiative for East and Southern Africa (ESA). However, scaling innovations is context-specific and complex, and requires nurturing existing and new partnerships. It will be important to take stock of the existing scaling experiences, constraints and opportunities across the ESA region and to explore whether patterns, communalities and differences. This is an internal survey that aimed at gathering scaling perceptions and experiences from ESA staff and core partners. The results are meant to (i) identify common scaling implementation challenges that need to be tackled, and (ii) inform an ESA science of scaling research agenda as a basis for fund-raising and implementation from 2023 onwards. This PowerPoint includes the preliminary results from the internal survey during the ‘week of scaling’ that was held in Nairobi in November 2022.